Shoot and root branch growth angle control — the wonderfulness of lateralness. (February 2015) - Roychoudhry, Suruchi; Kepinski, Stefan
Highlights: Gravitropic setpoint angles are growth angles that are maintained relative to gravity. Non-vertical branch growth is an important adaptive trait that is poorly understood. Auxin is central to the gravity-dependent, non-vertical growth of lateral branches. Non-vertical GSAs arise via balancing gravitropic and antigravitropic components. Abstract : The overall shape of plants, the space they occupy above and below ground, is determined principally by the number, length, and angle of their lateral branches. The function of these shoot and root branches is to hold leaves and other organs to the sun, and below ground, to provide anchorage and facilitate the uptake of water and nutrients. While in some respects lateral roots and shoots can be considered mere iterations of the primary root-shoot axis, in others there are fundamental differences in their biology, perhaps most conspicuously in the regulation their angle of growth. Here we discuss recent advances in the understanding of the control of branch growth angle, one of the most important but least understood components of the wonderful diversity of plant form observed throughout nature.